Buckling of compressed plates with closed-section longitudinal stiffeners: Two new mathematical models for resistance prediction. (October 2021) - Haffar, Muhammad Ziad; Kövesdi, Balázs; Adany, Sándor
Abstract: Longitudinally stiffened plates appear in many structural engineering applications. One of the typical failure modes is induced by the buckling of the stiffeners, therefore enhancing our understanding of buckling behavior is of crucial importance. Recently, buckling resistance of longitudinally stiffened plates with trapezoid stiffeners has been investigated by numerous research projects. A large amount of capacity prediction data is available for stiffened plates with diverse geometries, obtained by advanced shell finite element analyses. In the research reported in this paper such data have been collected from two recent researches. Two mathematical models have been worked out for calculation of the load-bearing capacity, by curve fitting technique. The first developed method is similar to the Direct Strength Method: a single reduction factor is applied on the gross cross-section resistance in order to get the buckling resistance, and the reduction factor is calculated by one single Winter-type formula. The second method is based on the Effective Width Method, but for the middle part of the stiffened plate a further reduction factor is applied, which reduction factor is obtained from one single Ayrton-Perry-type formula. Though the two mathematical models show some differences in certain cases, they give very similar results, both leading to satisfactorily precise resistance values. The mathematical models have been applied to study buckling behavior, in order to understand how the plate geometry influences the resistance. The proposed mathematical models are potentially applicable in design calculations.